A literature review to investigate the link between psychosocial characteristics and treatment adherence in cancer patients - Paraskevi Theofilou; Helen Panagiotaki (Oncology Reviews, 2012)
Adherence to medication has been recognized as a key issue in health outcomes and efforts to improve patients’ adherence are being made by the pharmaceutical industry, experts, and government bodies alike. This paper presents a review of these issues according to previous descriptive findings. Relevant studies written in English, published in 1976 or later, were identified through Medline, Embase and PsycInfo databases and reviewed. Review articles and clinical trials were excluded; all observational studies and surveys were considered. Articles were reviewed for any discussion of patients’ characteristics and psychosocial characteristics affecting adherence to cancer treatment. The search strategy included a combination of key words adherence and cancer in titles. The major findings are summarized and presented under two main headings: i) patients’ characteristics; and ii) psychosocial characteristics. In general, factors associated with increased likelihood of adherence to cancer treatment included younger age, higher education, higher income and Caucasian ethnicity. With regards to the psychosocial factors, lower levels of depression and anxiety, optimism as well as social support seemed to have a positive effect on treatment adherence. Studies of patterns of care in cancer treatment can help identify challenges in health care provided to particular subgroups of cancer patients and can aid researchers in designing studies that account for such factors in clinical and outcomes’ research.